Arctic Pollution Issues: A State of the Arctic Environment Report - Arctic Council, Arctic Monitoring ans Assessment Programme (AMAP) (Arctic Monitoring and Assessment program (AMAP), 1997)
A condensed version of the scientific/technical AMAP Assessment Report, presenting the information in a clear and readable manner for the non-scientific audience; richly illustrated and prefaced by an Executive Summary with recommendations specifically addressed to Ministers of the eight Arctic countries.